CP Antenna Array With Switching-Beam Capability Using Electromagnetic Periodic Structures for 5G Applications - Mohamad Mantash (IEEE Access, 2019)
This paper proposes a novel circularly polarized electromagnetic band-gap (EBG) antenna array backed by an artificial magnetic conductor (AMC) that operates in the 26-32-GHz bands. The designed antenna is a 2 x 2 Yagi-Uda antenna array that uses the directors' semicircles to direct the radiation in the horizontal end-fire direction. The feeding of the array is designed with two parallel T-junction portions forming a parallel feeding network that converts the polarization from linear to circular. An AMC is placed underneath the antenna to suppress the backward radiation and obtain the propagation only in the +z plane. The novel approach is based on the fact that EBGs are placed around the array to give to the antenna, beamswitching capability. This simple technique provides a high beam tilting angle of +90° from the end-fire to the full broadside plane. The final EBG-AMC-antenna array is circularly polarized and presents, at 29 GHz, a gain of 11.9 dBi, and an axial ratio bandwidth of 10% from 28 to 31 GHz. By assessing the high antenna performances presented in this paper, and the high angle beam-switching capability by adding the EBG, the novel array could be seen as a potential candidate for implementation in future 5G applications.